Prevalence of anemia among school going adolescents in Thiruvallur district, Tamil Nadu - Dev, Sathish; Valli, Sugantha; Kumar, Amar Nagesh (International Journal Of Community Medicine And Public Health, 2023)
Background: Nutritional anemia, with iron-deficiency anemia as the most prevalent type, is a pressing global health concern, impacting two billion people worldwide. Among vulnerable groups, school-going adolescents aged 10 to 17 years require special attention due to the critical phase of growth and development during this period. This study aims to assess the prevalence of anemia and its association with sociodemographic factors among adolescents in Thiruvallur district, Tamil Nadu. Methods: A cross-sectional study was conducted among 900 adolescent girls, utilizing a multistage sampling technique. Hemoglobin levels were measured using one-touch blood sampling, and physical examinations were performed by trained healthcare professionals. A structured questionnaire collected sociodemographic information, dietary habits, and lifestyle factors. Results: The study revealed a concerning prevalence of anemia, with 60% of the participants affected. Among these, 41.3% experienced moderate anemia, while 18.4% had mild anemia, and 0.4% had severe anemia. A significant correlation was observed between anemia prevalence and low socio-economic status among the participants. Conclusions: The high prevalence of anemia among adolescent girls in Thiruvallur district underscores the urgency of targeted interventions and public health initiatives to address this critical health issue. Improving nutrition, healthcare access, and socio-economic conditions are crucial steps in combating anemia's impact on school-going adolescents. Collaborative efforts from policymakers, healthcare providers, and community organizations are essential in eradicating nutritional anemia and enhancing the health and prospects of adolescents in the studied region.